2018
DOI: 10.1159/000491079
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Dysphagia and Diabetes Mellitus: Screening of 200 Type 1 and Type 2 Patients in Cairo, Egypt

Abstract: Background: Although diabetes mellitus is a well-researched systemic endocrinal disease, literature is scarce addressing the co-occurrence of oropharyngeal dysphagia with diabetes. Objective: The aim of this work was to screen Egyptian diabetic patients for symptoms suggestive of oropharyngeal dysphagia using the validated Arabic version of the Eating Assessment Tool (A-EAT-10). Participants and Methods: 200 Egyptian adult diabetic patients, aged from 18 to 59 years participated in the study. The inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
10
1
1
Order By: Relevance
“…Only one other study, to our knowledge, employed the T-EAT-10 questionnaire in this population. In the study by Zakaria et al [10], 200 patients with diabetes were recruited and the abnormal swallowing score obtained from the questionnaire was found to be 17.5%, which was relatively close to ours (22.3%). On the other hand, the most common swallowing complaint was “I cough when I eat” (80%) in Zakaria’s study but for the present study, it was “swallowing solids takes extra effort” (81.4%).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Only one other study, to our knowledge, employed the T-EAT-10 questionnaire in this population. In the study by Zakaria et al [10], 200 patients with diabetes were recruited and the abnormal swallowing score obtained from the questionnaire was found to be 17.5%, which was relatively close to ours (22.3%). On the other hand, the most common swallowing complaint was “I cough when I eat” (80%) in Zakaria’s study but for the present study, it was “swallowing solids takes extra effort” (81.4%).…”
Section: Discussionsupporting
confidence: 85%
“…Considering the outcomes of the previous studies, it is possible to say that patients with T2DM frequently have gastrointestinal problems and DM-related deglutition disorders [11, 26, 27]. Further, it has been reported in several studies that neuropathy-like complications related to diabetes lead to swallowing disorders [10, 12, 13, 28, 29]. However, to the best of our knowledge, there is a limited number of studies investigating the safety and efficiency of oropharyngeal swallowing in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients are very often on a broad spectrum of drugs that were not considered, especially antihypertensives and diuretics with anticholinergic effects causing xerostomia. Though the literature is scarce, an analysis of the co-occurrence of OD with diabetes via a simple questionnaire in younger patients found that being female and age progression were risks for OD 29 . More convincing is the diabetes-associated esophageal dysphagia, which was not integrated in our screening analysis.…”
Section: Discussionmentioning
confidence: 99%
“…11 A screening study on oropharyngeal dysphagia and diabetes mellites in Cairo, Egypt by Zakaria et al found that age progression and female sex were the risk factors for dysphagia. 12 In most of the cases, dysphagia aggravates with uncontrolled diabetes which can contribute to autonomic/peripheral neuropathy. All these studies point towards the significance of careful treatment of comorbidities in elderly for better assessment of treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%